Structural investigations of (Mn, Dy) co-doped ZnO nanocrystals using X-ray absorption studies. Issue 89 (15th December 2017) - Tiwari, N.; Kumar, S.; Ghosh, A. K.; Chatterjee, S.; Jha, S. N.; Bhattacharyya, D.
Abstract : EXAFS measurements on sol gel derived (Mn, Dy) co-doped ZnO nanocrystals show that oxygen vacancies are created near the Dy sites into ZnO lattice. Thus, oxygen vacancy assisted bound magnetic polarons contribute to the RTFM in the Dy doped samples. Abstract : (Mn, Dy)-doped ZnO nanocrystals with Mn-concentrations of 0 and 2% and Dy-concentrations of 0, 0.5%, 1%, 2%, 4% and 6% have been prepared using a sol–gel technique. Preliminary structural characterisations of the samples have been carried out using X-ray diffraction (XRD), Transmission Electron Microscopy (TEM) and Fourier Transformed Infra-red (FTIR) spectroscopy. Changes in the luminescence characteristics of the samples due to rare earth doping have been investigated by Photoluminescence (PL) measurement and its effect on the magnetic properties of the samples has also been studied. The local structure at the host (Zn) and dopant (Mn and Dy) sites of the samples have been thoroughly investigated by synchrotron based X-ray absorption spectroscopy (XAS), which is an element specific microscopic technique comprising both X-ray near edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) measurements and the magnetic properties of the samples have been explained in light of the findings from XANES and EXAFS.